2016
DOI: 10.1021/acsami.6b03458
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lithium Additives in Small Molecule Light-Emitting Electrochemical Cells

Abstract: Light-emitting electrochemical cells (LEECs) utilizing small molecule emitters such as iridium complexes have great potential as low-cost emissive devices. In these devices, ions rearrange during operation to facilitate carrier injection, bringing about efficient operation from simple, single layer devices. Recent work has shown that the luminance, efficiency, and responsiveness of iridium-based LEECs are greatly enhanced by the inclusion of small amounts of lithium salts (≤0.5%/wt) into the active layer. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 46 publications
3
30
0
Order By: Relevance
“…Earlier work on iridium‐based LEEC devices showed that the dielectric constant and the thickness of the EDL changed with Li[PF 6 ] additive concentration . As the percentage of Li[PF 6 ] was increased, the dielectric constant also increased.…”
Section: Resultsmentioning
confidence: 95%
“…Earlier work on iridium‐based LEEC devices showed that the dielectric constant and the thickness of the EDL changed with Li[PF 6 ] additive concentration . As the percentage of Li[PF 6 ] was increased, the dielectric constant also increased.…”
Section: Resultsmentioning
confidence: 95%
“…It has been revealed that electron injection/transport (n‐type doping) are usually much less efficient than hole injection/transport (p‐type doping) in blue LECs incorporating ionic iridium complexes. [ 23,61,65,66 ] It is shown here that the host‐guest LEC with an exciplex host largely promotes electron injection and transport (thus n‐type doping) through the acceptor molecules. It can be concluded that enhancement of PQLY of the active layer and facilitation of n‐type doping (thus establishment of p‐i‐n junction) both contribute to the high performances of host‐guest blue LECs with an ionic exciplex host.…”
Section: Resultsmentioning
confidence: 96%
“…It has been reported that addition of ionic liquid or salt into the active layer of LEC could accelerate the formation of ohmic double layers at the electrode/active layer interfaces and the establishment of p‐i‐n junction, leading to enhanced device performances. [ 23,61 ] An ionic liquid, tetrahexylammonium tetrafluoroborate ([THA][BF 4 ]), was then added into the active layers of device B. The resultant device structure is ITO/PEDOT: PSS (40 nm)/tBuCAZ‐ImMePF 6 : TRZ‐ImEtPF 6 : [THA][BF 4 ]: 10 wt% [Ir(buoppy) 2 (dmapzpy)]PF 6 (100 nm)/Al (100 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The test also showed a driving voltage that approached 4 V at the end of the 1000 h test as a result of voltage drift. In small‐molecule or ionic‐transition metal (ITMC) LECs, added lithium salt has been shown to improve the response and luminance of the cells . These studies all point to the importance of salt concentration in LEC operation.…”
Section: Discussionmentioning
confidence: 99%